Ecotoxicological testing of sediments and dredged material : an overlooked opportunity? - Susanne Heise; Marc Babut; Carmen Casado; Ute Feiler; Benoit J. D. Ferrari; Laura Marziali (Journal of soils and sediments, 2020)
Purpose: Basing decisions for the management of contaminated sediments on ecotoxicological data is still often met with skepticism by European stakeholders. These concerns are discussed as they pertain to bioassays to show how ecotoxicological data may provide added value for the sustainable management of sediment in aquatic systems. Materials and methods: Five “concerns” are selected that are often raised by stakeholders. The ecotoxicological practice is discussed in light of the knowledge gained in recent decades and compared with chemical sediment analysis and chemical data. Results and discussion: Common assumptions such as a higher uncertainty of biotest results for sediments compared to chemical analyses are not supported by interlaboratory comparisons. Some confusion also arises, because the meaning of biotest data is often misunderstood, questioning their significance in light of a limited number of organisms and altered test conditions in the lab. Because biotest results describe a sediment property, they should not be directly equated with an impact upon the biological community. To identify a hazard, however, the possibility of false-negative results due to the presence of contaminants that are not analyzed but are toxic is lower. Conclusions: The cost of increased investment in ecotoxicological tests is, in our view, small compared with that of making false-negative assessments of sediment/dredged material that can ultimately have long-term environmental costs. As such, we conclude that ecotoxicological testing is an opportunity for sediment management decision-making that warrants more attention and confidence in Europe.
Keywords: Bioassays; Ecotoxicological testing; Sediment; Stakeholders